Quantum Circuit Learning for Uncertainty Quantification of RELAP5 Code Analysis of ROSA/LSTF Small Break LOCA Tests - Kinoshita Ikuo (EPJ Web of Conferences)
To reduce the computational demand in the best estimate plus uncertainty (BEPU) analysis, an accurate and inexpensive machine learning model is expected to be used to replace the high-fidelity RELAP5 code for rapid determination of the uncertainties on the figure of merit of interest. One of the problems associated with the application of a machine learning is overlearning. Quantum circuit learning is the quantum analogue of classical deep learning, which is expected to be less prone to overlearning because the optimized parameters are bound by unitary transformations in the quantum circuit. In this paper, quantum circuit learning is applied to the BEPU analysis of the fuel peak cladding temperature (PCT) for a small-break LOCA scenario in PWRs. The parameterized quantum circuit is trained using a small number of the RELAP5 analysis results and the prediction accuracy of the 95th percentile value of the PCTs is investigated. By optimizing the multipliers of the measured basis, the 95th percentile value of the PCTs predicted by the quantum circuit learning resulted in better accuracy and smaller variability than order statistics and linear quadratic regressions.